PENGARUH OPINI GOING CONCERN DAN PERGANTIAN MANAJEMEN TERHADAP AUDITOR SWITCHING, REPUTASI AUDITOR SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2011-2015) - Gideon Saputra; Amir Hasan; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This purpose of this study was to examine effect of opinion going concern, management changes toward auditor switching and impact of auditor reputation as a moderating impact on the opinion going concern and management exchanges toward auditor switching. The population that will be used in this research are manufacturing companies that listed in Indonesia Stock Exchange period 2011-2015. Sample in this study choosen by purposive sampling method with criteries that the companies have done auditor switching outside regulation, and have an independent auditor's report every year. Based on purposive sampling method, the number of manufacturing companies sample in this study were 22 companies, with 5 years observation therefore number of sample in this study were 110 observation. The analysis technique used is logistic regression analysis and moderated regression analysis wuth SPSS vers 21. The result of this study indicate that opini going concern and management exchange has positive effect toward auditor switching , auditor reputation is not able to modierate the effect opini going concern and management exchnges toward auditor switching. With the result that if auditor were give opinion going concern and companies have to management exchanges so the probability that auditor will be changes, and result also indicate that auditor reputation can’t influence decision that not change auditor if he given opinion going concern and if companies have to management changes.Keyword : opinion going concern, management exchanges, auditor switching, and auditor reputation